Multiple perspectives of concurrent engineering and their integration. (4th October 2004) - Bowonder, B.; Bhuyan, S.; Sharma, K.J.
Concurrent Engineering is a process of integrated and parallel development of a product for reducing the product development cycle time. This approach to product development has been used for reducing the idea to market cycle time. The strategies, processes and results that lead to a tight product development cycle evolved over a period of time. This paper attempts to integrate the various concepts to map the evolution of concurrent engineering.